فاعلية البرنامج الارشادي الانتقائي في تنمية السمات الشخصية الايجابية لدى طلاب فكلتي التربية الرياضية جامعة كوية - عبدلله, د.خالد حسين; كريم, ژوان عادل (Sulaimani Journal for Humanities, 2023)
The current research aims to identify the effect of a selective counseling program on the development of some positive personality traits among students of the Faculty of Physical Education / Koya Universit, And the experimental method was used to achieve the objectives of the research. A counseling program was prepared according to the techniques of positive psychology, consisting of (16) sessions, and it was applied by two sessions per week, with a time of one session (60) minutes. Some positive personality traits according to the techniques and methods used in applying it to students, and showed a significant difference in the mean scores of the control and experimental groups in the post-test in favor of the experimental group.
Keywords: البرنامج الارشادي السمات الايجابية طلاب التربية البدنية والعلوم الرياضية